PENGARUH PENDEKATAN KOMUNIKATIF DENGAN BANTUAN MEDIA VIDEO TERHADAP KEMAMPUAN MENULIS PUISI DI SEKOLAH DASAR - Fitri, Rausan Fikri Futurity El; Syamsiati, Syamsiati; Nursyamsiar, Nursyamsiar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract:This research intended for describe the effect of the communicative approach through video on the 5th grade student skills in writing poetry at Sekolah Dasar Negeri 16 Pontianak Kota. The method used in this research is the Non Randomized Control Group Pretest-Posttes Design experiment. The tools used to collect data in this study were observation sheets and tests. The technique used is direct observation and measurement. The sample of this research is 5th grade students, totaled 55 students. The results of data processing using the Mann Whitney U-Test with the normal curve approach obtained zcount = 2.59 for the 0.025 error level obtained ztable of 1.96 thus zcount> ztable or 2.59> 1.96, it can be concluded that there are differences in results write poetry on the 5th grade student at Sekolah Dasar Negeri 16 Pontianak Kota. Based on the analysis of the effectiveness of the application of communicative approach through video on this research, obtained ES = 0.91 with a high category.Â Keywords: Communicative Approach, Writing Children's Poetry